Public attitudes towards automated external defibrillators: results of a survey in the Australian general population - Kovoor, Joshua G.; Marschner, Simone; Amarasekera, Anjalee; Nageswaran, Meera; Page, Gregory J.; Chow, Clara K.; Thiagalingam, Aravinda; Kovoor, Pramesh (Frontiers in Cardiovascular Medicine, 2023)
Background Swift defibrillation by lay responders using automated external defibrillators (AEDs) increases survival in out-of-hospital cardiac arrest (OHCA). This study evaluated newly designed yellow–red vs. commonly used green–white signage for AEDs and cabinets and assessed public attitudes to using AEDs during OHCA. Methods New yellow–red signage was designed to enable easy identification of AEDs and cabinets. A prospective, cross-sectional study of the Australian public was conducted using an electronic, anonymised questionnaire between November 2021 and June 2022. The validated net promoter score investigated public engagement with the signage. Likert scales and binary comparisons evaluated preference, comfort and likelihood of using AEDs for OHCA. Results The yellow–red signage for AED and cabinet was preferred by 73.0% and 88%, respectively, over the green–white counterparts. Only 32% were uncomfortable with using AEDs, and only 19% indicated a low likelihood of using AEDs in OHCA. Conclusion The majority of the Australian public surveyed preferred yellow–red over green–white signage for AED and cabinet and indicated comfort and likelihood of using AEDs in OHCA. Steps are necessary to standardise yellow–red signage of AED and cabinet and enable widespread availability of AEDs for public access defibrillation.